Supporting Child Growth from an Early Age: A Review of Ten Key Parenting Roles for Young Parents - Ismaniar Ismaniar; Setiyo Utoyo; Rembulan Catra Banyu Biru; Sri Murni (JETL (Journal of Education, Teaching and Learning), 2025)
The high rate of early marriage in recent years is a phenomenon that must be taken seriously by various parties. This problem will continue due to young parents' low readiness level to fulfil their role. Many young parents today lack an understanding of their role in being responsible for the growth and development of their children after marriage. This study uses a literature review, searching through various relevant offline and online references. The results of this study indicate that non-formal education programs, such as parenting programs, can provide a platform for young parents to enhance their readiness to fulfil their roles in addressing issues related to early childhood growth and development stimulation. Parenting programs can provide the knowledge, attitudes, and skills necessary to become effective parents, and they can play a crucial role in supporting the growth and development of children from an early age.